2013
DOI: 10.12988/asb.2013.3831
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanine ammonialyase gene expression and activity in relation to lignin deposition in salt stressed aeluropus littoralis

Abstract: Phenylalanine ammonia-lyase is the first enzyme of phenylpropanoid pathway and has an important role on plant cell wall lignification. The influence of different concentrations (0, 200 and 400 mM) of NaCl on growth, lignin content and PAL gene expression and activity were investigated at different internode positions (first ,fourth and seventh internodes) in a halophyte grass, Aeluropus littoralis (Gouan) parl. Salt stress inhibited the growth, increased the PAL mRNA level and induced PAL activity as well as l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In corn, expression of phenylalanine amonyalase (PAL,EC 4.3.1.5), encoding the first enzyme of the shikimate pathway, was transiently elevated under salinity, suggesting a role for this enzyme in decreasing the oxidative stress imposed by salinity (Gholizadeh and Kohnehrouz 2010). Kelij et al 2013 showed that enhanced PAL expression was a reliable marker for better tolerance to saline conditions, and could be an important candidate for the biotechnological improvement of stress tolerance in crops. Moreover, PAL is the first committed step in the biosynthesis of phenolics, which provide substrates to enzymes of the flavonoid pathway, such as chalcone synthase (CHS,EC 2.3.1.74) and flavonols synthase (FLS,EC 1.14.11.23), which are involved in the biosynthesis of flavonols, including kaempferol, quercetin, and myricetin (Winkel-Shirley 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In corn, expression of phenylalanine amonyalase (PAL,EC 4.3.1.5), encoding the first enzyme of the shikimate pathway, was transiently elevated under salinity, suggesting a role for this enzyme in decreasing the oxidative stress imposed by salinity (Gholizadeh and Kohnehrouz 2010). Kelij et al 2013 showed that enhanced PAL expression was a reliable marker for better tolerance to saline conditions, and could be an important candidate for the biotechnological improvement of stress tolerance in crops. Moreover, PAL is the first committed step in the biosynthesis of phenolics, which provide substrates to enzymes of the flavonoid pathway, such as chalcone synthase (CHS,EC 2.3.1.74) and flavonols synthase (FLS,EC 1.14.11.23), which are involved in the biosynthesis of flavonols, including kaempferol, quercetin, and myricetin (Winkel-Shirley 2001).…”
Section: Introductionmentioning
confidence: 99%